1981
DOI: 10.1152/ajpheart.1981.241.2.h283
|View full text |Cite
|
Sign up to set email alerts
|

Closed-chest electrode-catheter technique for His bundle ablation in dogs

Abstract: A modified quadripolar electrode catheter that had two-thirds of the distal surface insulated with high-voltage plastic was inserted in 10 dogs. After a His bundle potential had been recorded, a synchronized direct-current electrical discharge was delivered between the electrodes showing the largest His bundle deflection using a standard direct-current defibrillator, and a metallic plate was positioned over the dog's back. Complete atrioventricular (AV) block was induced in 9 of 10 dogs, which were followed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 0 publications
0
29
0
2
Order By: Relevance
“…In comparison with prior irreversible treatments such as alcohol injection and surgical transection, cryothermal energy offered the major advantage of the ability to identify the appropriate target area and observe for functional effect following the application of cryothermal energy prior to production of an irreversible lesion. Initially, all approaches were surgical in nature, until a ''closed chest'' 35,36 was developed, which is known today as the transvenous approach. Initial practice with the closed chest approach deviated away from the use of cryothermal energy and instead employed direct current (DC) energy [37][38][39] and laser.…”
Section: Novel Ablation Modalities On the Horizonmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with prior irreversible treatments such as alcohol injection and surgical transection, cryothermal energy offered the major advantage of the ability to identify the appropriate target area and observe for functional effect following the application of cryothermal energy prior to production of an irreversible lesion. Initially, all approaches were surgical in nature, until a ''closed chest'' 35,36 was developed, which is known today as the transvenous approach. Initial practice with the closed chest approach deviated away from the use of cryothermal energy and instead employed direct current (DC) energy [37][38][39] and laser.…”
Section: Novel Ablation Modalities On the Horizonmentioning
confidence: 99%
“…Initially, all approaches were surgical in nature, until a ''closed chest'' 35,36 was developed, which is known today as the transvenous approach. Initial practice with the closed chest approach deviated away from the use of cryothermal energy and instead employed direct current (DC) energy [37][38][39] and laser. 40 Results were largely encouraging; however, complications from these approaches, namely barotrauma and perforation, respectively, lead to the study and application of radiofrequency (RF) energy.…”
Section: Novel Ablation Modalities On the Horizonmentioning
confidence: 99%
“…In the early 1980s, Scheinman (Gonzalez et al 44 ) and Gallagher et al 45 demonstrated that a high-energy shock delivered over a catheter placed against the bundle of His could interrupt AV conduction to create chronic, complete AV block. Although this treatment had a relatively restricted application for patients with atrial arrhythmias, such as atrial fibrillation with an uncontrolled rapid ventricular rate, it introduced the concept of being able to alter the electrophysiology of the heart with a catheter.…”
Section: Catheter Ablationmentioning
confidence: 99%
“…Herein we report the short-and long-term electrophysiologic effects of low-energy (<30 J) direct-current shocks for ablation of the canine AV conduction system with a suction electrode catheter and correlate these with the histologic changes in the AV conduction system. FIGURE 1. A, The suction ablation catheter has a central lumen with a suction port and two electrodes.…”
mentioning
confidence: 99%